The Implementation of Acute Respiratory Infection (ARI) Controlling Programme and the Coverage of Pneumonia among Under-Five Children - Baroya, Ni'mal; Aryani, Maulidya Puji; Ariyanto, Yunus (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2018)
Abstract Pneumonia is an acute infection of lung tissue (alveoli). Pneumonia is one of the main focus ARI preventing and controlling program.  One of the ARI preventing and controlling program indicators was pneumonia coverage among under five years old. The coverage of pneumonia finding among under five years old in Banyuwangi Regency since 2014-2016 years have not reached the national target. Pneumonia toddler coverage in 2014 and 2015 shows 33,7% and 71,1%, while in 2016 shows 41,99%. This research aims to analyze the association between officer characteristics, logistics availability and ARI control activities with pneumonia toddler coverage in Banyuwangi Regency. The research uses cross sectional analytic desain with 31 respondents. The result of this research has significant relationship is age, work length and capacity buailding. Nevertheless, gender, education, knowladge, availability of diagnostic tools, guideline, KIE media, recording and reporting media, advocation and socialisation, pneumonia find and management, supervision, recording and reporting, partnership and network, monitoring and evaluation has not significant relationship. Banyuwangi Health Office is hoped to do conduct periodic training every year to ARI program officer on ARI control management, management of pneumonia toddler and promotion of pneumonia control in under fives to increase human resources capacity in primary health facility.                 Abstrak Pneumonia merupakan salah satu fokus utama Program Pencegahan dan Pengendalian ISPA. Salah satu indikator program P2 ISPA adalah cakupan penemuan pneumonia balita. Cakupan pneumonia pada balita di Kabupaten Banyuwangi dari tahun 2014-2016 belum mencapai target nasional. Pada tahun 2014 dan 2015 cakupan pneumonia pada balita sebesar 33,7% dan 71,1% sedangkan tahun 2016 sebesar 41,99%. Penelitian ini bertujuan menganalisis hubungan antara karakteristik petugas, ketersediaan  logistik dan kegiatan pengendalian ISPA dengan cakupan penemuan pneumonia pada balita di Kabupaten Banyuwangi. Desain penelitian yang digunakan adalah analitik cross sectional dengan jumlah sampel 31 responden. Hasil penelitian ini yang memiliki hubungan signifikan dengan cakupan penemuan pneumonia pada balita adalah usia, lama kerja dan peningkatan kapasitas SDM dengan cakupan penemuan pneumonia pada balita. Sedangkan jenis kelamin, pendidikan, pengetahuan, ketersediaan alat diagnostik, buku pedoman, media KIE, media pencatatan dan pelaporan, advokasi dan sosialisasi, penemuan dan tata laksana pneumonia, supervisi, pencatatan dan pelaporan, kemitraan dan jejaring serta monitoring dan evaluasi tidak memiliki hubungan. Dinas Kesehatan Kabupaten banyuwangi diharapkan dapat melaksanakan pelatihan secara berkala setiap tahun kepada pemegang program P2 ISPA mengenai manajemen pengendalian ISPA, tatalaksana pneumonia pada balita serta promosi pengendalian pneumonia pada balita untuk meningkatkan kapasitas sumber daya manusia yang telah tersedia di puskesmas.